PENERAPAN METODE OBJECTIVE MATRIX (OMAX) UNTUK MENGANALISIS PRODUKTIVITAS DI PT. NUSANTARA BETA FARMA PADANG - Gamindra Jauhari; Meldia Fitri; Aulia Sri Darma Nova (Ensiklopedia of Journal, 2019)
Productivity is one of the important factors to support the survival of a company by analyzing and evaluating the output obtained based on the level of performance during a certain period. PT. Nusantara Beta Farma Padang is a company engaged in pharmaceuticals with superior products with powdered Salisil Talk Wangi. To find out the productivity level of the current production section, it is necessary to measure productivity, because the results of this productivity measurement can be used as a consideration to implement efforts that can be done to increase the productivity of the company. Productivity measurement is done by using the objective matrix (OMAX) method. The criteria used in this study are raw material productivity, effective working hours productivity, machine working hours productivity and production effectiveness. The highest productivity value achieved during the measurement in the period April to December 2016 is in October with a productivity level of 878 and the lowest achieved in July of 140. The cause and effect diagram is used to determine the cause of the decline in the production of fragrant salisil talk. Factors that cause decreased productivity are damage to filling machines, inappropriate raw materials, and operators who are less skilled. Decrease in productivity analysis is done using a causal diagram to get a design solution to increase the productivity of the production section.